2011
DOI: 10.1128/aem.00018-11
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Campylobacter spp. in California Gull (Larus californicus) Excreta

Abstract: We examined the prevalence, quantity, and diversity of Campylobacter species in the excreta of 159 California gull (Larus californicus) samples using culture-, PCR-, and quantitative PCR (qPCR)-based detection assays. Campylobacter prevalence and abundance were relatively high in the gull excreta examined; however, C. jejuni and C. lari were detected in fewer than 2% of the isolates and DNA extracts from the fecal samples that tested positive. Moreover, molecular and sequencing data indicated that most L. cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Hence, alternative approaches have been explored, and despite continued efforts, no robust E. coli nor enterococci markers have been reported (Field et al 2003;Jiang et al 2007;Whitman et al 2007;Mohapatra et al 2008;Lanthier et al 2010). There are promising bird markers, however, which come from Catellicoccus 16S rRNA gene markers (Lu et al 2011;Green et al 2012;Ryu et al 2012a, b), and one demonstrated to identify Sandhill Crane excreta (Ryu et al 2012a, b) was used and supported in the current study (Table 1). A further line of evidence comes from the limited detection of Bacteroidetes in Sandhill Crane and Snow Goose excreta compared to other animal/human fecal sources, which has also been reported for other avian species (Lu et al 2007(Lu et al , 2008(Lu et al , 2009Gourmelon et al 2007;Dubinsky et al 2012).…”
Section: Key Markers Of Crane Pollutionsupporting
confidence: 50%
See 1 more Smart Citation
“…Hence, alternative approaches have been explored, and despite continued efforts, no robust E. coli nor enterococci markers have been reported (Field et al 2003;Jiang et al 2007;Whitman et al 2007;Mohapatra et al 2008;Lanthier et al 2010). There are promising bird markers, however, which come from Catellicoccus 16S rRNA gene markers (Lu et al 2011;Green et al 2012;Ryu et al 2012a, b), and one demonstrated to identify Sandhill Crane excreta (Ryu et al 2012a, b) was used and supported in the current study (Table 1). A further line of evidence comes from the limited detection of Bacteroidetes in Sandhill Crane and Snow Goose excreta compared to other animal/human fecal sources, which has also been reported for other avian species (Lu et al 2007(Lu et al , 2008(Lu et al , 2009Gourmelon et al 2007;Dubinsky et al 2012).…”
Section: Key Markers Of Crane Pollutionsupporting
confidence: 50%
“…For example, Escherichia coli O157:H7 and other waterborne enteric pathogens including Cryptosporidium, Giardia, and Campylobacter spp. have been detected in the excreta of various migratory gull species, Canada geese, and Whistling swans (Gould and Fletcher 1978;Demaré et al 1979;Waldenström et al 2002;Wetzel and Lejeune 2007;Graczyk et al 2008;Lu et al 2011). So, while as few as 30 ring-billed gulls (Larus delawarensis) may impact on the microbial water quality of a waterbody as measured by fecal indicator bacteria (FIB; Lévesque et al 2000), the real concern is their potential co-introduction of potentially pathogenic species to humans and other animals.…”
mentioning
confidence: 99%
“…in gull excreta (29,31,40). On the other hand, Lu et al (26) reported high prevalence of campylobacters in California gulls (i.e., 45% positive in 159 fecal samples) but a low occurrence of pathogenic species based on speciesspecific PCR assays and 16S rRNA gene sequences. Based on the latter results, the risk associated with gull fecal pollution has been estimated to be relatively low (35), suggesting that, compared to human fecal pollution sources, fecal loads from gulls and other waterfowl will have to be high in order for the risks to be significant.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial and viral pathogens have been isolated from different species of birds, and examples of their zoonotic transmission have been documented (14,15,22,24,26,28,35,36), although the overall frequency of zoonotic transmission of human pathogens by avian species is still poorly understood. For example, while a high prevalence of campylobacters in gull excreta (i.e., 45% positive in 159 fecal samples) was previously observed (22), the low occurrence of pathogenic campylobacter species is considered to represent a relatively low level of risk for human infection (32). However, Pacha et al (27) reported that human-pathogenic Campylobacter jejuni isolates were detected in more than 70% of sandhill crane and duck excreta samples.…”
Section: Resultsmentioning
confidence: 99%